What is cultural evolution anyway?. (1st April 2022) - Micheletti, Alberto J C; Brandl, Eva; Mace, Ruth
Abstract: The term cultural evolution has become popular in the evolutionary human sciences, but it is often unclear what is meant by it. This is generating confusion and misconceptions that are hindering progress in the field. These include the claim that behavioral ecology disregards culture. We argue that these misunderstandings are caused by the unhelpful use of term cultural evolution to identify both a phenomenon—culture changing through time—and a theory to explain it—the potential role of cultural transmission biases in driving this change. We illustrate this point by considering recently published influential studies and opinion pieces. If we are to avoid confusion, the term cultural evolution is best reserved to identify the phenomenon of cultural change. This helps clarify that human behavioral ecologists do not disregard culture, but instead have studied its evolution from the very beginning. Different approaches to the study of human behavior can coexist and complement each other in the framework offered by Tinbergen's four evolutionary questions. Clarifying key terms is crucial to achieve this synthesis. Abstract : We argue that the term cultural evolution is confusing because it is being used to identify both a phenomenon and a theory. It should be reserved for the phenomenon. In this way, it becomes clear that the behavioral ecology approach does not disregard culture, as is often erroneously suggested. Different approaches to studying cultural behaviors can and should coexist because they address different, but complementary, evolutionary questions about mechanism, ontogeny, function, and phylogeny.